Bioeconomy: Pectinases Purification and Application of Fermented Waste from Thermomyces Lanuginosus - Makky, Essam A.; M. M., Yusoff (Engineering and Technology Publishing, 2015)
Malaysia takes a step forward to promote and support the development of sustainable and green technology by adopting and master the technology holistically. Bioeconomy refers to all economic activity derived from scientific and research activity focused on biotechnology. Pectin degradation enzymes are widely used in the industrial processing of fruits and vegetables in order to decrease the viscosity of juices and thus to facilitate extraction, maceration, liquefaction, filtration and clarification processes. Sugar-cane bagasse (SCB) is agrowaste produced in large quantities in our environment used as the substrate for Exo-polygalacturonase (Exo-PG) from Thermomyces lanuginosus at 55°C under solid-state fermentation (SSF) culture. Exo-PG was purified using Gelfiltration chromatography and exhibited only one sharp peak. Biotechnological applications of fermented waste obtained, mixed with the fungal biomass at 55°C as biofertilizer at different concentrations (w/w) were cultivated with Zea mays for 30 days to indicate the plant growth on sandy soil and succeeded to induce the growth which may give an indication of applying the present biofertilizer particularly in the reclaimed sandy soils. Only 14 amino acids were detected and obviously that Exo-PG was typical proline containing enzyme.